2018
DOI: 10.3390/pathogens7030061
|View full text |Cite
|
Sign up to set email alerts
|

An Extract Purified from the Mycelium of a Tomato Wilt-Controlling Strain of Fusarium sambucinum Can Protect Wheat against Fusarium and Common Root Rots

Abstract: An approach to manage seed-transmitted Fusarium crown-foot-root rot (FCR, Fusarium spp.) and common root rot (CRR, Bipolaris sorokiniana) on wheat, avoiding environmental risks of chemicals, is seed treatments with microbial metabolites. F. sambucinum strain FS-94 that induces resistance to tomato wilt was shown by this study to be a source of non-fungitoxic wheat-protecting metabolites, which were contained in a mycelium extract purified by gel-chromatography and ultrafiltration. Plant-protecting effect of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 63 publications
0
24
0
2
Order By: Relevance
“…After an overnight incubation at 30 • C at a slight automated agitation, acetonitrile was added to a final concentration of 84%, and the suspensions were extracted at vigorous shaking for 30 min. ZEN was further purified from the extract as described earlier [60]. The precipitate obtained after the evaporation of the purified ZEN-containing extract on a rotary evaporator was dissolved in a minimum volume of a methanol-acetonitrile mixture (1:1) and analyzed by reversed-phase HPLC.…”
Section: Decontamination Testmentioning
confidence: 99%
“…After an overnight incubation at 30 • C at a slight automated agitation, acetonitrile was added to a final concentration of 84%, and the suspensions were extracted at vigorous shaking for 30 min. ZEN was further purified from the extract as described earlier [60]. The precipitate obtained after the evaporation of the purified ZEN-containing extract on a rotary evaporator was dissolved in a minimum volume of a methanol-acetonitrile mixture (1:1) and analyzed by reversed-phase HPLC.…”
Section: Decontamination Testmentioning
confidence: 99%
“…The highest concentration of difenoconazole in our experiments reflected the commercial fungicidal dosage recommended for grain treatments with Dividend R to protect wheat and barley plants against Fusarium and common *Seeds were surface-disinfect before treatments as described earlier (Shcherbakova et al, 2018). **Non-disinfect seeds naturally infected by fungal root rot agents.…”
Section: Improved Protective Efficacy Of Triazoles Combed With Thymolmentioning
confidence: 77%
“…Upon completion of the cultivation, DON and ZEN were quantified by reverse phase HPLC using a Waters 1525 Breeze HPLC system equipped with a Waters 2487 UV detector, applying isolation procedures slightly modified from those described previously (Shcherbakova et al, 2018;Stakheev et al, 2018). Briefly, the submerged culture of each experimental or control flask was extracted twice with an equal volume of ethyl acetate or dichloromethane (to isolate ZEN or DON, respectively) for 1-h on an incubator shaker at 220 rpm and 25 • C. Mycelia were separated by centrifugation and dried at 102 • C up to a constant weight.…”
Section: Mycotoxin Quantification In Submerged F Culmorum Culturesmentioning
confidence: 99%
“…The protective effect of the resistance-inducing metabolites from F. sambucinum (isolate FS-94) was assayed as described (Shcherbakova et al, 2018). Briefly, 50 surface-sterilized T. kiharae seeds were incubated in the FS-94 elicitor metabolites for 3 h as described above and infected with F. oxysporum by soaking in the fungal spore suspension for 30 min, whereupon, seeds were placed on filter paper towels, which were rolled up and put in beakers with distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier, we showed that the intracellular elicitor metabolites produced by the biocontrol Fusarium sambucinum (isolate FS-94) protect wheat from Stagonospora nodorum causing glume/leaf blotch as well as from multiple fungi belonging to the pathogenic root rot complex ( F. culmorum , F. avenaceum , F. oxysporum , F. sporotrichioides , F. gibbosum , and Bipolaris sorokiniana ) (Shcherbakova et al, 2012; Shcherbakova et al, 2018) and induce systemic resistance in plants (Shcherbakova et al, 2011; Shcherbakova et al, 2018). In this work, to further analyze the mode of action of the resistance elicitors from F. sambucinum and to elucidate the role of defensins, one of the most important AMP family, in induced resistance (IR), we used global transcriptome sequencing (RNA-seq) of wheat seedlings treated with the elicitors and displaying IR.…”
Section: Introductionmentioning
confidence: 99%